2019
DOI: 10.1371/journal.pone.0211271
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking a high bacterial diversity in the coralloid root microbiome from the cycad genus Dioon

Abstract: Cycads are among the few plants that have developed specialized roots to host nitrogen-fixing bacteria. We describe the bacterial diversity of the coralloid roots from seven Dioon species and their surrounding rhizosphere and soil. Using 16S rRNA gene amplicon sequencing, we found that all coralloid roots are inhabited by a broad diversity of bacterial groups, including cyanobacteria and Rhizobiales among the most abundant groups. The diversity and composition of the endophytes are similar in the six Mexican s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 85 publications
11
37
1
Order By: Relevance
“…In terms of alpha diversity, there was not a consistent difference between organic and conventional management systems, a pattern that was also observed for corn . Alpha diversity results were consistent with studies that have demonstrated the highest alpha diversity of both Fungi and Prokaryotes in the soil (Lebreton et al, 2019;Suárez-Moo et al, 2019). Additionally our results were consistent with previous results from the same site which demonstrated that the highest within plant alpha diversity for Prokaryotes could be found in the roots, but for Fungi the root alpha diversity was similar to that of the leaves (Gdanetz and Trail, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In terms of alpha diversity, there was not a consistent difference between organic and conventional management systems, a pattern that was also observed for corn . Alpha diversity results were consistent with studies that have demonstrated the highest alpha diversity of both Fungi and Prokaryotes in the soil (Lebreton et al, 2019;Suárez-Moo et al, 2019). Additionally our results were consistent with previous results from the same site which demonstrated that the highest within plant alpha diversity for Prokaryotes could be found in the roots, but for Fungi the root alpha diversity was similar to that of the leaves (Gdanetz and Trail, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The cyanobacterial sequences from Panamanian Zamia belong to a single clade based on rb-cL-rbcX. Our study is in line with findings in the Mexican cycad genus Dioon where cyanobionts were also monophyletic using 16S rRNA (Gutiérrez-García et al, 2018;Suárez-Moo et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Our results support the suggestion that there may exist some specialization for symbiosis in the Nostoc taxa inhabiting the coralloid roots of cycads (Cuddy et al, 2012;Suárez-Moo et al, 2019;Zimmerman & Rosen, 1992) or perhaps a biogeographical structure may be present in cycads.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also note that recent work (e.g., Gutiérrez‐García et al, ; Zheng, Chiang, Huang, & Gong, ; Suarez‐Moo, Vovides, Griffith, Barona‐Gomez, & Cibrian‐Jaramillo, ) has revealed additional taxonomic diversity in coralloid roots beyond the dominant cyanobacterial strains that are typically described (i.e., Nostoc and Calothrix ), including other diazotrophic bacteria such as rhizobia. While it is not known whether these other taxa contribute significant amounts of nitrogen to the host plant, our coupled pure culture and foliar δ 15 N dataset suggests that any additional nitrogen supply to cycad tissues has an isotopic composition similar to that of the cyanobacterial isolates.…”
Section: Discussionmentioning
confidence: 60%